1998
DOI: 10.1046/j.1523-1755.1998.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Apa I polymorphism in the vitamin D receptor gene may affect the parathyroid response in Japanese with end-stage renal disease

Abstract: Vitamin D [1,25(OH)2D3] plays a key role in the pathogenesis of secondary hyperparathyroidism. A polymorphism in the vitamin D receptor (VDR) gene is reported to be involved in bone mineral density and the serum level of intact-osteocalcin (i-OC) in patients with osteoporosis. We investigated the relationship between VDR gene polymorphisms and the levels of intact PTH (i-PTH) and i-OC in 129 Japanese patients with end-stage renal disease (ESRD). The VDR gene sequences were PCR-amplified, and the product was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The association of the ApaI polymorphism in the VDR gene with bone and mineral metabolism has been investigated in hemodialysis patients. Yokoyama et al (1998) reported that serum PTH and osteocalcin levels among patients with the CC genotype were almost twice as high as in patients carrying the A allele. Consistent with their results, our study revealed that the C allele of the ApaI polymorphism is significantly associated with ESRD risk.…”
Section: Discussionmentioning
confidence: 99%
“…The association of the ApaI polymorphism in the VDR gene with bone and mineral metabolism has been investigated in hemodialysis patients. Yokoyama et al (1998) reported that serum PTH and osteocalcin levels among patients with the CC genotype were almost twice as high as in patients carrying the A allele. Consistent with their results, our study revealed that the C allele of the ApaI polymorphism is significantly associated with ESRD risk.…”
Section: Discussionmentioning
confidence: 99%
“…In all subjects, genomic DNA was extracted from peripheral leukocytes. The polymerase chain reaction products were digested at the intron between exon 8 and exon 9 with restriction enzyme Apa I, using two primers that recognized 740 base pairs of the VDR gene [11]. …”
Section: Methodsmentioning
confidence: 99%
“…There have been some reports on the relationship between VDR gene polymorphism and bone mineral metabolism in osteoporosis patients [6, 7, 8]. Recently, there have also been reports on the relationship between VDR polymorphism and parathyroid hormone (PTH) as well as bone mineral density in ESRD patients subjected to renal replacement therapy [9, 10, 11, 12, 13]. We have previously indicated the possibility of the influence of Apa I fragment length polymorphism of the VDR gene on onset and progression of secondary hyperparathyroidism in Japanese ESRD patients [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several polymorphic sites have been described within VDR gene. Polymorphism near the 3' end of VDR gene identified by restriction enzyme BsmI, TaqI, ApaI, and FokI associated with osteoporosis [17], Type 1 diabetes mellitus [18], polycystic ovary syndrome [19], end-stage renal disease [20], several types of carcinoma such as breast, prostate, and colon carcinoma [21]. Therefore, genetic disparities of prematurity with regards to VDR gene polymorphism need to be investigated.…”
Section: Introductionmentioning
confidence: 99%